Helicobacter spp. in Necropsied Southern Sea Otters (Enhydra lutris nereis) Is Associated With Gastric Ulcers and Sensitive to Multiple Antibiotics - Batac, Francesca I.; Miller, Melissa A.; Moriarty, Megan E.; Shen, Zeli; Fox, James G.; Ottemann, Karen M. (Frontiers in Marine Science, 2020)
Southern sea otters (Enhydra lutris nereis) are threatened marine mustelids that commonly have gastric ulcers with secondary hemorrhage (melena) as a contributing cause of death. Although Helicobacter spp. infections are known to cause gastric ulcers and gastritis in humans and ferrets, it is unknown if the sea otter bacterium, ‘H. enhydrae’ sp. nov., causes similar gastric pathology. Determining whether Helicobacter detection is associated with sea otter gastric pathology is the first step toward using this information to expedite diagnosis and treatment. We investigated the proportion of Helicobacter infections in 46 necropsied southern sea otters via quantitative real-time polymerase chain reaction (qPCR) of the 16S rRNA gene. Helicobacter DNA was detected in fresh-frozen and formalin-fixed gastric body and pyloric tissues using Helicobacter genus-specific 16S rRNA primers. Data from gross necropsy and histopathology were analyzed for associations between Helicobacter detection via qPCR, and presence/absence of gastric pathology. ETEST gradient strips were utilized to investigate antimicrobial minimum inhibitory concentrations for H. enhydrae isolates. Helicobacter spp. were detected in the gastric tissue of 85% of sea otters in this study. Fresh-frozen samples were more commonly Helicobacter qPCR-positive than formalin-fixed tissue, indicating variable sensitivity of detection in relation to post-necropsy tissue processing methods. Diagnosis of gastric ulcers at necropsy was significantly associated with Helicobacter qPCR detection in gastric mucosa (P= 0.005), while age, sex, presence of melena, shark trauma, and protozoal infection were not associated (P> 0.1). H. enhydrae strains were sensitive to clarithromycin and tetracycline in vitro at physiologically relevant concentrations. Overall, this work suggests that Helicobacter spp. might be commonly found in southern sea otters, particularly those with ulcers, and that H. enhydrae can be treated with several commonly used anti-Helicobacter therapies.